Gaps in end-of-life care and lack of support for family carers in Poland and Central Eastern Europe - Krakowiak, Piotr (Palliat Care Soc Pract, 2020)
The growth of life expectancy in Central Eastern Europe and increase in the number of older people in that region are the consequences of changes in the 1990s period, connected to transition from the communism into a market economy. Central Eastern Europe is already facing consequences of fast ageing and insufficient development of state health care and social services. Those result in gaps in the provision of end-of-life care and overburden of family caregivers. This essay addresses gaps in end-of-life care, showing the development of hospice-palliative care on one side, and highlighting main problems with long-term care on the other. There is scarce support for informal caregivers and lack of cooperation between health and social care. End-of-life care is over medicalized in hospice-palliative care and hardly existing in long-term care. Dying is more a social than medical event, and as such, it should be cared for by compassionate communities, encouraging cooperation of professionals with family caregivers and society. Unfortunately, to date, there is no adequate cooperation in social dimension of end-of-life care in most of Central Eastern Europe. The social dimension of end-of-life care has to be recognized and empowered with the health promoting palliative care and introduction of compassionate communities in Central Eastern Europe.